The effectiveness of school administration and its relation to improving the performance of teachers in primary education A field study on a sample of primary schools in Tipaza - zitouni, sabira; dilmi, raouia (Journal of Social Sciences and Humanities, 2024)
This study aims to explore the effectiveness of school management and its relationship with improving teacher performance in primary education, because school management is an important factor in improving education quality and improving teacher efficiency. This study covers several aspects, from the definition and characteristics of school management, to its strategies and their impact on educational performance. The results of the study show that effective school administration depends on a set of basic elements such as effective communication, professional support, motivation, and providing an appropriate educational environment. The results showed that these elements directly affect the performance of professors, by enhancing their teaching abilities and developing their skills. Some challenges facing school administration were also identified, such as lack of resources, administrative pressures, and lack of professional training. The study also showed that there is a positive relationship between educational leadership methods and progress in teachers' performance, as management that adopts participatory and interactive leadership methods contributes to raising the level of teacher performance and improving the quality of education in general. Therefore, the study recommends the need to enhance cooperation between school administration and teachers and provide appropriate training programs to develop their skills, thus contributing to improving the academic performance of students in primary education. This study also seeks to provide new insights that contribute to enhancing the effectiveness of school administration and improving the quality of education in the future.